Switching Stable Kidney Transplant Recipients to a Generic Tacrolimus Is Feasible and Safe, but It Must Be Monitored - Fernando González; René López; Elizabeth Arriagada; René Carrasco; Natalia Gallardo; Eduardo Lorca (Journal of Transplantation)
Background. Tacrolimus is the primary immunosuppressive drug used in kidney transplant patients. Replacing brand name products with generics is a controversial issue that we studied after a Chilean Ministry of Health mandate to implement such a switch. Methods. Forty-one stable Prograf (Astellas) receiving kidney transplant patients were switched to a generic tacrolimus (Sandoz) in a 1 : 1 dose ratio and were followed up for up to 8 months. All other drugs were maintained as per normal practice. Results. Neither tacrolimus doses nor their trough blood levels changed significantly after the switch, but serum creatinine did: 1.62±0.90 versus 1.75±0.92 mg/dL (p<0.001). At the same time, five graft biopsies were performed, and two of them showed cellular acute rejection. There were nine infectious episodes treated satisfactorily with proper therapies. No patient or graft was lost during the follow-up time period. Conclusion. Switching from brand name tacrolimus to a generic tacrolimus (Sandoz) is feasible and appears to be safe, but it must be monitored carefully by treating physicians.